Development of Pasta Products with Nonconventional Ingredients and Their Effect on Selected Quality Characteristics: A Brief Overview - R. A. T. Nilusha; J. M. J. K. Jayasinghe; O. D. A. N. Perera; P. I. P. Perera (International Journal of Food Science)
Pasta is a widely consumed food in all over the world. Coarse semolina obtained from durum wheat and water are the main ingredients of conventional pasta products. The amount of gluten and quality level of durum wheat, are two important factors for the superiority of finished pasta. Market price of durum wheat is higher than the common wheat and it contributes no more than 5% of the world wheat production. Thus, to come across the challenge of emerging pasta consumption, new field of research that is dealing with the incorporation of nonconventional ingredients to the conventional formula of pasta has initiated. The compositions of raw materials which are used for pasta preparation directly affect the physical, chemical, and textural properties of the product. Therefore, incorporation of nonconventional ingredients can lead to a contradictory effect of pasta quality. This review will focus on the various types of nonconventional ingredients that are being incorporated in pasta products and their effect on the quality attributes of different pasta products.